(3OjhGf QGVj GdbRhjfjs - (3QGVj Hf UGdM Hf egOj Hf QVG Hf eMeO Ydj GdMSjfj GdbRhjfj GdHZOGOj,J (B1387 (3g` s ((3eMeO WGgQ GdSeGhj s)
(3ChdgG (B:s
(3bGd eNeSkG heSeWkG GdaRObjI HeG hUd Edjg aj eOM Rjf GdYGHOjf Ydjg GdSdGe(B: (3jGefcQkG ef CeGf Gddg eOMJg hCKHJ Gddg aj GdCYfGb HjYJg s
(3BNQgG (B:s
(3jMb dfG GdHcGA hakG HSGO Hg CHJOd GdCSi hGdUHQ YqRi hgd jLOj GdHcG MbkG dRQA CejQ GdeDefjf Hg GdeYRi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B106 s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI HGdfLa (B(291) s
Keywords: (3GdCOHs